Library User Education: Powerful Learning, Powerful Partnerships - Dewey, Barbara I. (Rowman & Littlefield Publishers, 2002)
...Material presented here is replete with concrete new ideas not only for collaboration, but also for funding, training, personal involvement, Web-based instruction, and other concepts too numerous to mention. And the best thing about these ideas is that they are not the usual endlessly-discussed theories_these are ideas that have worked_and some which have failed_in the real world...Despite the myriad new works available today related to library instruction in general and information literacy in particular, none is devoted solely to collaborative efforts between teaching faculty and librarians. This is where Library User Education: Powerful Learning, Powerful Partnerships shines_just as in the real world, it's all about collaboration.' _Angela Weiler, Portal